(untitled) (Contemporary Journal of Social Science Review, 2024)
The rapid pace of urbanization has resulted in extensive artificial lighting, leading to pervasive light pollution that disrupts ecological processes within urban environments. This study investigates the impact of light pollution on plant circadian rhythms, emphasizing its effects on urban flora and critical plant-pollinator interactions. A mixed-method approach was employed to gather data across various plant species in both urban and rural settings, allowing for comparative analysis. The findings indicate that urban plants exposed to artificial lighting exhibit notable disruptions in their growth patterns and flowering cycles, which in turn alter their interaction dynamics with nocturnal pollinators. These results underscore the importance of implementing sustainable lighting policies in urban areas to mitigate ecological imbalances and promote biodiversity.